A Strategic Pathway to Green Digital Shipping - Mohsen Khabir; Gholam Reza Emad; Mehrangiz Shahbakhsh; Maxim A. Dulebenets (Logistics)
Background: The maritime industry is undergoing a profound transformation to meet global decarbonization goals. As Industry 4.0 advanced digital technologies are increasingly integrated into shipping operations, the role of the human element is evolving significantly. This intersection of decarbonization, digitalization, and human element/workforce transformation lays the foundation for more structured initiatives such as Green Digital Shipping Corridors (GDSCs), a strategic solution to scale zero-emission, smart maritime routes. Methods: This paper explores the interconnected roles of decarbonization, digitalization, and human capital development through a systematic literature review. It examines how these pillars converge in the implementation of GDSCs, drawing on academic and industry sources to identify challenges and opportunities in workforce readiness, policy integration, and technological adoption. Results: The findings underscore the necessity of coordinated action across the three pillars, particularly highlighting the importance of structured training programs, cross-sector collaboration, and standardized regulations. GDSCs are presented as an applied framework to align these transitions, enabling scalable, digitally enabled, low-emission maritime routes. Conclusions: There is a significant gap in current research that holistically connects the human factor with technological and environmental imperatives in the context of maritime transformation. This paper addresses that gap by introducing GDSCs as a strategic outcome of integrated change, providing actionable insights for policymakers, industry leaders, and educators aiming to advance sustainable shipping.